Quantification of rupture directivity effects on strong ground motion during the 8 January 2022 MS6.9 Menyuan earthquake in Qinghai, China - Xie, Junju; Wang, Wencai; An, Zhao; Li, Kewei; Tian, Xiufeng; Wu, Lina; Gao, Shude; Zhang, Weidong; Yuan, Jie (Frontiers in Earth Science, 2023)
On January 8, 2022, an MS6.9 earthquake occurred in the Menyuan County, Qinghai Province at the northeastern margin of the Tibetan Plateau. A dense observatory network consisting of accelerographs and intensity meters has obtained many acceleration recordings in this region, which previously had only a few strong motion recordings. Using acceleration data recorded by 141 accelerographs and micro-electro mechanical system (MEMS)-based intensity meters within 100 km of the causative fault, we investigated the spatial distribution and attenuation characteristics of the near-source ground motion during this event. The observed response spectra were compared with the prediction obtained using the NGA-West2 models. It was found that, in the long-period section of >1.0 s, the acceleration response spectra in the rupture forward direction (southeast of the epicenter) were greater than the prediction, while observations on the northwest side were lower than the prediction. Through the spatial distribution of the ground motion and quantitative analysis of the residuals, we found that the rupture directivity effects on the ground motions were controlled by the spatial azimuth relative to the fault and the along-strike projected length of the rupture, which mainly affected the long-period portion of the >1.0 s. In the rupture forward direction, the spectral accelerations (SAs) with periods of 1.0–10.0 s were enhanced to 1.18–1.56 times the average. In the backward direction (northwest of the epicenter), the SAs with periods of 1.0–10.0 s were only 0.63–0.86 times the average. The rupture directivity effects during the MS6.9 (MW6.6) earthquake exhibited an obvious period-dependence and narrowband characteristics, and the amplification effects were the strongest at 5.0 s. The amplification factors in the straight forward directions were underestimated by the empirical model. Two typical velocity pulse records were observed in the rupture forward direction, and their response spectra were significantly amplified at long periods of greater than 1.0 s, with peak amplification values of 4.0–6.0 near the characteristic period of the pulses. This amplification was related to the resonance excited by a specific periodic pulse.